Cannabinoid CB1 receptor binding and acetylcholinesterase inhibitory activity of Sceletium tortuosum L. - Lubbe, A.; Khatib, Alfi; Yuliana, Nancy Dewi; Jinap, Selamat; Verpoorte, Robert (Universiti Putra Malaysia, 2010)
The whole plant extract of plant Sceletium tortuosum, plant native to South Africa, has been known traditionally to have mood enhancing and stimulant properties. These properties have been confirmed before by proving serotonin-uptake inhibition activity. A further confirmation by using CB1 receptor binding assay has been performed in this study. The unfermented alkaloid extract was proved to posses a higher activity to bind CB1 receptor compared to that of the fermented one. GC-MS analysis confirmed that unfermented alkoloid extract contain more alkaloids than the fermented one. The methanol extract was also more active than the fermented one, suggesting that non-alkaloid compounds in this extract could posses this activity. An additional test to check wether this extract can improve cognitive function and memory was performed by acetylcholinesterase inhibitory assay. Both fermented and unfermented alkaloid extracts could inhibit acetylcholinesterase with IC50 being 0.303 mg/ml and 0.330 mg/ml, respectively. However, the major alkaloid in the extract, mesembrine, did not show inhibition of the enzyme. A TLC based test proved that other alkaloids in the extract were responsible to the activity